2021
DOI: 10.3390/medicina57010073
|View full text |Cite
|
Sign up to set email alerts
|

Severe Atrophy of the Ipsilateral Psoas Muscle Associated with Hip Osteoarthritis and Spinal Stenosis—A Case Report

Abstract: Pathology of the lumbar spine and hip joint can commonly coexist in the elderly. Anterior and lateral leg pain as symptoms of hip osteoarthritis and spinal stenosis can closely resemble each other, with only subtle differences in both history and physical examinations. It is not easy to identify the origin of this kind of hip pain. The possibility of hip osteoarthritis should not be underestimated, as this could lead to an incorrect diagnosis and inappropriate spinal surgery. We report the case of a 54-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Mak, et al, who strove to determine if there is significant psoas muscle atrophy as indicated by muscle cross-sectional area and a high degree of fat infiltration in post-unilateral hip arthroplasty cases over an eight-year period found the cross-sectional area of the psoas muscle on the implant side was significantly smaller than that on the non-operative side [32]. There was also an association between the cross-sectional area differences and the fat grade of the implant side, results that aligned somewhat with those of Lee, et al, [16].…”
Section: Search Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Mak, et al, who strove to determine if there is significant psoas muscle atrophy as indicated by muscle cross-sectional area and a high degree of fat infiltration in post-unilateral hip arthroplasty cases over an eight-year period found the cross-sectional area of the psoas muscle on the implant side was significantly smaller than that on the non-operative side [32]. There was also an association between the cross-sectional area differences and the fat grade of the implant side, results that aligned somewhat with those of Lee, et al, [16].…”
Section: Search Resultssupporting
confidence: 75%
“…These as well as those published over time are highly diverse however, and include, but are not limited to studies examining aspects of muscle measurements, muscular strength deficits, aberrant movement patterns, muscle fat infiltration, and intervention studies. Various studies discussing muscle atrophy in the context of one or more hip muscles and that may have implications for hip osteoarthritis prevention and intervention do however prevail, for example studies that discuss atrophy of the iliopsoas muscle or the hip abductor muscles in hip osteoarthritis realms [14][15][16][17].…”
Section: Search Resultsmentioning
confidence: 99%
“…A trophy and weakness of the psoas muscle have been reported as clinical manifestations of both lumbar spinal stenosis, secondary to neurogenic compromise of the L2-4 spinal roots, as well as hip osteoarthritis due to "disuse" atrophy of the muscle caused by restricted movement of the hip joint (12)(13)(14). However, this is the first case describing severe psoas muscle atrophy as late consequence of a vertebral fracture.…”
Section: Discussionmentioning
confidence: 92%